Does Postmenstrual Age Affect Medical Patent Ductus Arteriosus Treatment Success in Preterm Infants? - Kaur, Sharandeep; Stritzke, Amelie; Soraisham, Amuchou Singh (American Journal of Perinatology, 2019)
Objective Patent ductus arteriosus (PDA) is the most common cardiovascular problem of prematurity. Our objective was to examine the effect of postmenstrual age (PMA) on response to medical PDA treatment.Study Design This retrospective cohort study included infants ≤ 32 weeks' gestational age (GA) who received nonsteroidal anti-inflammatory drugs (NSAIDs) for PDA treatment. Response was positive if echocardiogram showed closed or small PDA or no further treatment was required. Baseline characteristics between responders and nonresponders were compared. Multivariable logistic regression analysis with generalized estimating equations was used to analyze the association between PMA and response.Results A total of 183 infants with a mean GA of 26.4 ± 2.2 weeks and birth weight of 870 ± 313 g received 257 courses of NSAIDs. Positive response rate to the first course was 65.6%. Two and three courses were given in 62 and 12 infants, with response rates of 48.4 and 50%, respectively. Surgical ligation of PDA occurred in 30 (16.4%) infants. Multivariable logistic regression analysis with generalized estimating equations revealed that PMA was not associated with a positive response (adjusted odds ratio [aOR]: 0.88; 95% confidence interval [CI]: 0.71–1.10). GA at birth remained the most influential factor (aOR: 1.33; 95% CI: 1.02–1.73).Conclusion GA rather than PMA is the strongest predictor for a positive response in medical PDA treatment.
Keywords: patent ductus arteriosus; postmenstrual age; NSAIDs; treatment; efficacy